(untitled) (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
Industrialization and globalization have caused a huge burden on the limited natural resources, which releases various environmental pollutants such as toxic metal ions and pesticides. World Health Organisation (WHO) has set a maximum permissible limit for these toxic pollutants in water, above which, it is unsuitable for drinking purpose. There are various techniques available for the determination of such pollutants like ICP-MS, HPLC, FAAS etc. that are costly, cumbersome, and time consuming. Whereas, electrochemical sensors are portable, fast and can perform multi-analyte sensing. Electrochemical sensor can be made selective by fabricating with nanocomposites having different functional groups. Nowadays, trend of utilizing greener materials in research field is being highly appreciated in accordance with the principles of green chemistry for the application and development of electrochemical sensors. Ionic liquids having non-volatility, low toxicity, wide potential window, high electrochemical stability and conductivity have shown sustainable electrochemical sensing applications. Nanocomposite of these ionic liquids as a sensing platform have been extensively used in electrochemical detection of various pollutants. This work provides a literature survey of different ionic liquid nanocomposite based sensing platform for electrochemical detection of toxic pesticides and heavy metals. They have demonstrated good sensitivity with detection limit below WHO guidelines.